LEVEL OF DEPRESSION AMONG POST STROKE PATIENTS IN A STATE OF ANDHRAPRADESH - K. Thulasi Ram; Dr. Nagarathanam M. (Indian Journal of Psychiatric Nursing)
The study was aimed to assess the level of depression among post stroke patients attending neurology OPD SVIMS, Tirupathi. A cross sectional descriptive design was adopted and 170 post stroke patients after 3 months onset of acute stroke was selected by non-probability sampling technique and screened for cognitive deficits by Folstein mini mental status examination and post stroke patients who scored more than and equal to 19 were screened for level of depression by 17 - item Hamilton depression rating scale. The study results showed among 170 patients with a mean age of 54.84 + 10.9 years, 32.9% (56) of post stroke patients were having very severe depression, 27.1% (46) have moderate depression, 24.1% (41) have mild depression, 11.8% (20) have severe depression, 4.1%(7) patients are without any depressive symptoms. The association of demographic variables with level of depression showed educational status(r=-0.64), occupational status(r=-0.416), family income (r=-0.289), care giver health status(r =-0.176) were negatively correlated with level of depression at p< 0.01 level. Place of residence (r = 0.299) were positively correlated at p< 0.01, source of family income (r=0.153) were positively correlated p<0.05 level, care giver suffering with illness (r=-1.69) were negatively correlated at p<0.05 level.